The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.biomaterials.2010.03.065
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancement of human embryonic stem cell osteogenic differentiation with nano-fibrous scaffolding

Abstract: Human embryonic stem cells (hESC) hold great promise as a cell source for tissue engineering since they possess the ability to differentiate into any cell type within the body. However, much work must still be done to control the differentiation of the hESC to the desired lineage. In this study, we examined the effects of the nano-fibrous (NF) architecture in both two dimensional (2-D) poly(Llactic acid) (PLLA) thin matrices and 3-D PLLA scaffolds in vitro to assess their affect on the osteogenic differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(84 citation statements)
references
References 49 publications
1
83
0
Order By: Relevance
“…This suggests cooperative enhancement of L1 signaling on subcellular scales of substrate geometry, a phenomenon that deserves further mechanistic analysis. Scaffold topography has been shown to influence and enhance cellular responses, [65][66][67] as the 3-D architecture better emulates in vivo conditions compared to 2-D thin films.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests cooperative enhancement of L1 signaling on subcellular scales of substrate geometry, a phenomenon that deserves further mechanistic analysis. Scaffold topography has been shown to influence and enhance cellular responses, [65][66][67] as the 3-D architecture better emulates in vivo conditions compared to 2-D thin films.…”
Section: Discussionmentioning
confidence: 99%
“…Setting the joint site as an example, this site exhibits less host responses to implant, because more body fluids and faster fluid exchange are helpful for removing the acidic degradation products effectively. In fact, many positive results of tissue repairing using PLA or PLGA porous scaffolds have been reported [27][28][29][30]48,49]. Our group has recently revealed that the body fluid exchanged faster than we initially supposed, even at the subcutaneous site, for a block copolymer hydrogel composed of PLGA-PEG-PLGA with initial pH 4 became neutral just ten hours after a subcutaneous injection into SD rats [50].…”
Section: Is There Any Significant Difference Of Cytotoxicity Between mentioning
confidence: 93%
“…That is why polyesters have been studied for a long time [14][15][16][17][18][19][20]. A lot of efforts have been done on improving the biocompatibility of the polyester porous scaffolds [21][22][23][24][25][26][27][28], and examinations of their medical applications [27][28][29][30][31][32][33].…”
mentioning
confidence: 99%
“…Similarly, another study demonstrated that mouse ES cells can be induced to differentiate into specific neural lineages, that is, neurons, oligodendrocytes, and astrocytes, when seeded onto electrospun fibrous scaffolds (Xie et al, 2009). In another study, the nanofibrous architecture of the substrate enhanced the osteogenic differentiation of human ES cells compared to a more traditional scaffolding architecture (Smith et al, 2010). Thus, surface engineering approaches that alter the topographical structure of the substrate surface can be used to modulate ES cell behavior and fate.…”
Section: Control Of Cells By Geometric Modificationmentioning
confidence: 97%